The Health of the worker / by the Rt. Hon. J. Ramsay MacDonald, M.P. - Macdonald, James Ramsay, 1866-1937
1927-07-04 1927 1920s 1 page THE HEALTH OF THE WORKER. By the Rt. Hon. J. Ramsay MacDonald, M.P. There never was a time in the history of the country when more attention was given to subjects of health than at present. There are many organisations dealing with specialised aspects of health, all of which are making an appreciable contribution to the well being of the community. The Ministry of Heaith has been very active in this direction. The British Medical Association is alive to its importance, and is at present considering how best it can assist in making known in a popular way the laws necessary to observe if good health is to be maintained. Medical Officers of Health are more active than ever in seeking to combat the illnesses to which human life has ever been subjected. It is a truism to say "Health is Wealth," but no doubt health is the truest form of wealth for the nation and for the individual. It is stated on good authority that since the reign of Queen Victoria the life of the average citizen has been lengthened by at least ten years, and this is due in great measure to the activities of the various organisations referred to, and also to more enlightened views on the part of the members of the community. Medical Science was for long chiefly engaged in curing sickness and disease, but the medical profession has given more attention lately to preventive measures, and the discoveries of science have done much to relieve us of much disease which our forefathers knew not how to avoid. Still, in spite of all that has been done, and is being done, there is much room and need for yet greater efforts being put forth to educate the public on how to prevent, or at least mitigate, the evils of sickness and disease. This is evident when one considers that in 1924 (the latest available figures) no less than twenty-six million weeks' work was lost among insured workers alone through sickness and disablement, 50 per cent. of which, it is calculated, was avoidable had the workers had and used the available knowledge. Consider what this represents in loss of wages and production, not to speak of the vast amount of pain, suffering, and discomfort that the unfortunate had to bear. It has been truly said that on matters of health all humanity reaches the same level. Rich and poor, learned and unlearned, are all subject to the ailments which afflict the human body. Much as the nation is agitated on political, social, and industrial subjects there cannot be any controversy or difference of opinion when the health of the nation or the individual is concerned. Apart from the usual sicknesses to which all are subject, the industrial workers in almost all trades and industries have to bear the special sicknesses and diseases which are incidental to their occupations. Medical and Factory Inspectors and all enlightened employers of labour are keen to combat these evils, yet in spite of all their efforts a great deal depends on the individual both knowing and caring for his health. Laws and regulations are good, but the individual has to carry them out. To give the necessary information to the workers how to prevent or at least mitigate the occupational sicknesses and diseases, the Industrial Health Education Society has created an organisation covering England, Scotland, and Wales. Already in the course of two years over 300 meetings have been held with workers' organisations dealing with the special sicknesses and diseases incidental to particular groups of workers. These meetings have been addressed by competent medical men, who have hitherto given their services gratuitously. That these services have been much appreciated is evidenced by the large audiences, by the keenness with which workers have asked questions, and by renewed requests for other such meetings. Appreciating the nature and value of this propaganda, the Trades Union Congress General Council have recommended the activities of this Society to all its affiliated Unions and their branches, and is represented on each of the five Area Councils, the remaining members of the Councils being almost entirely members of the medical profession. The services of the Society are given free. As one of the Vice-Presidents of the Society I have pleasure in commending the work of this Society not only to the industrial and other workers but also to employers of labour, who doubtless find that it pays to have healthy workers, and workers who are not only more efficient, but less likely to meet with accidents. Further particulars of the Society's work may be had from the Industrial Health Education Society, 84 Kingsway. London, W.C.2, or 89 Millbrae Road, Langside, Glasgow. J. RAMSAY MACDONALD. 200/B/3/2/C693/1/9